The Influence of Overweight on the Structural and Geometric Parameters of the Left Ventricular Myocardium and the Daily Blood Pressure Profile in Middle-aged Military Personnel - Botirkhon Ravshanovich, Salikhov; Bakhromkhon Aniskhanovich, Alyavi (International Journal of Psychosocial Rehabilitation, 2020)
One of the leading risk factors for the development of arterial hypertension is undoubtedly overweight. The purpose of this study was to study the effect of excess body mass index on the structural and geometric parameters of the left ventricular myocardium and the daily blood pressure profile in middle-aged military personnel with arterial hypertension. The study included 73 patients suffering from arterial hypertension (AH) of 1-2 degrees, male, aged 20 to 45 years, with stage 1 hypertension. With an increase in the level of body weight in military personnel with hypertension, there is an increase in the incidence of remodeled left ventricular myocardium and an increase in the diagnosis of adverse daily blood pressure profiles. Based on the results of complex therapy (hypotensive therapy), it is also necessary to pay attention to actions that are aimed at normalizing body weight.